PERSEPSI PETANI TERHADAP PENYULUH DALAM PEMBERDAYAAN PETANI KENTANG PADA KELOMPOK TANI GEMAH RIPAH II DI DESA NGANTRU KECAMATAN NGANTANG KABUPATEN MALANG - Hendra, Hendra; Suwasono, Son; Kholil, Ahmad Yusuf (Universitas Tribhuwana Tunggadewi, 2016)
This study aims to determine farmers' perceptions of the efforts of extension workers in empowering potato farmers in the gemah ripah II farmer group in Ngantru Village, Ngantang District, Malang Regency. Perception is the process concerned about the entry of messages or information into the human brain, through human perceptions that are constantly in a relationship with their environment. This perception process occurs by looking at the processed results from the primary data obtained by direct interviews with potato farmers totaling 30 people and each farmer is asked as many as 15 questions and immediately answered then the results of the answers are processed using spss, The data processing aims to prove the perceptions of farmers towards the efforts of extension workers in empowering potato farmers in the gemah ripah 2 farmer group in Ngantru Village, Ngantang District, Malang Regency. Looking at the results of data processing, it can be concluded that the highest percentage of farmers' perceptions of the efforts of extension agents in empowering potato farmers is 48.67%. This shows that farmers' perceptions of the efforts of extension workers in empowering potato farmers in the Gemah Ripah II farmer group are good. Penelitian ini bertujuan untuk mengetahui persepsi petani terhadap upaya penyuluh dalam pemberdayaan petani kentang pada kelompok tani gemah ripah II di Desa Ngantru, Kecamatan Ngantang, Kabupaten Malang. Persepsi adalah proses yang bersangkutan tentang masuknya pesan atau informasi kedalam otak manusia, melalui persepsi manusia terus menerus menjalin hubungan dengan lingkungannya. Proses persepsi ini terjadi dengan melihat hasil olahan dari data primer yang didapatkan dengan cara wawancara langsung dengan petani kentang yang berjumlah 30 orang dan masing-masing petani di beri pertanyaan sebanyak 15 pertanyaan dan langsung di jawab kemudian hasil jawaban tersebut di olah dengan menggunakan spss, pengolahan data tersebut bertujuan untuk membuktikan persepsi petani terhadap upaya penyuluh dalam pemberdayaan petani kentang pada kelompok tani gemah ripah 2 di Desa Ngantru, Kecamatan Ngantang, Kabupaten Malang. Melihat dari hasil pengolahan data jadi dapat disimpulkan bahwa persentase tertinggi persepsi petani terhadap upaya penyuluh dalam pemberdayaan petani kentang 48,67%. Hal ini menunjukan persepsi petani terhadap upaya penyuluh dalam pemberdayaan petani kentang pada kelompok tani Gemah Ripah II adalah baik.